1980
DOI: 10.1159/000123000
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Treatment with Thyrotropin-Releasing Hormone (TRH) or an Analog of TRH (Linear <i>β</i>-Alanine TRH) on the Hypothalamic-Pituitary-Thyroid Axis

Abstract: The effects of treatment for 5 or 9 days with varying doses of thyrotropin-releasing hormone (TRH) or the linear β-alanine TRH congener (pGlu-His-Pro-β-Ala-NH2) on serum levels of TSH, T3 and T4 were studied in mice and rats. At low doses in rats treatment with TRH for 9 days significantly increased serum levels of T3 but not serum T4 whereas a higher dose of TRH (10 mg/kg) reduced serum T3 levels. β-ALA TRH (0.1–10 mg/kg IP) treatment for 9 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…The animals did not show any significant weight loss. The small increase in temperature observed during the first 2 days of treatment is difficult to be attributed to the thyroid hormones, since TRH was shown to influence directly the body temperature in rats [16], The following TSH decrease during the rest of our study is in agreement with the results of other au thors who have also reported a decreased TSH release in vitro [17] and in vivo [18] in rats and in man after repeated or chronic treatment with TRH [19][20][21], Most of these authors have used several doses of TRH ad ministered intravenously or orally at various time schedules. We used oral TRH in drink ing water, which is water soluble and stable and in addition has a longer biological halflife than the intravenous form.…”
Section: Discussionsupporting
confidence: 92%
“…The animals did not show any significant weight loss. The small increase in temperature observed during the first 2 days of treatment is difficult to be attributed to the thyroid hormones, since TRH was shown to influence directly the body temperature in rats [16], The following TSH decrease during the rest of our study is in agreement with the results of other au thors who have also reported a decreased TSH release in vitro [17] and in vivo [18] in rats and in man after repeated or chronic treatment with TRH [19][20][21], Most of these authors have used several doses of TRH ad ministered intravenously or orally at various time schedules. We used oral TRH in drink ing water, which is water soluble and stable and in addition has a longer biological halflife than the intravenous form.…”
Section: Discussionsupporting
confidence: 92%
“…However, it is not known whether TSH pulses depend on pulsatile thyrotropin-releasing hormone (TRH) secretion, in analogy to hypothalamic control of gonadotropin and growth hormone (GH) pulses (3,4). Con¬ tinuous TRH infusions in humans and animals cause initial increases in TSH levels, which diminish despite continued TRH administration (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). A more recent study has also shown greater TSH release when TRH is given in intermittent, rather than continuous, fashion (19).…”
Section: Introductionmentioning
confidence: 99%
“…This response, noted in TRH infusion studies (5)(6)(7)(8)10,11,14,16,17), may interfere with the assessment of TSH pulses. This problem can be avoided by studying patients with primary hypothy¬ roidism, who cannot increase thyroid hormone synthesis in response to TRH. We hypothesized that pulsatile TSH secretion depends on pulsatile TRH input from the hypothalamus.…”
Section: Introductionmentioning
confidence: 99%
“…The subsequent decline and maintenance of lower levels could be explained by a combination of negative feedback and other regulatory mechanisms which are put in place upon recognizing abnormally high concentrations of these hormones. These mechanisms include downregulation of TRH receptors in the hypophysis [16] and direct reduction in TRH receptor numbers in response to elevated T 3 levels which then result in reduced production of TSH [17]. Further regulation can be also mediated by increased rate of hepatic [18] and peripheral [19] deiodination of thyroid hormones.…”
Section: Discussionmentioning
confidence: 99%